Pemahaman Dzat Allah (Analisis Perbedaan Metodologi al-Ghazali dalam Kitab al- Iqtishad fi al-I’tiqad dan dengan Muhadditsin) - Nurdin, Nur Dian Syah Fikri; Shidiq, M. Iskandar Rois; Muhammad Royyan Faqih Azhary; M. Farid Zaini (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2024)
Al-Iqtishad fi Al-I'tiqad is one of Al-Ghazali's works that reflects a moderate stance in matters of belief. It addresses the existence of groups with extremes, whether leaning too far left or right, such as the Mu'tazilah who are very rational in their approach, or the textualists who reject rationality, like the Hawasyiyah. Al-Ghazali tends to be a mediator, adopting both rationality and textualism as the foundation of his thought. This article is written to illustrate Al Ghazali's methodology of argumentation and its implementation in explaining modernist beliefs, particularly regarding arguments about the essence of God, which are often debated by extremist groups. Al Ghazali's views will be compared with those of the Muhadditsin in their understanding of texts related to the essence of God. The primary data for this article is sourced from Al-Ghazali's Al-Iqtishad fi Al-I'tiqad, which is explored and elaborated upon using content analysis methods. The findings of this article explain that Al-Ghazali's methodology of argumentation is divided into three parts. In the implementation of one of his methodologies, Al-Ghazali presents two premises to produce an argumentative and rational conclusion. Thus, in his argumentation, the issue of the essence of God will be more clearly addressed in the main discussion of this article. Keywords: Al-Ghazali, Al-Iqtishad fi Al-I’tiqad, The Essence of God